1992
DOI: 10.1128/jcm.30.2.362-369.1992
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic typing of Staphylococcus aureus by DNA restriction fragment length polymorphisms of rRNA genes: elucidation of the clonal nature of a group of bacteriophage-nontypeable, ciprofloxacin-resistant, methicillin-susceptible S. aureus isolates

Abstract: Analysis of DNA restriction fragment length polymorphisms of rRNA genes (ribotyping) was employed to assist in the epidemiologic investigation of the emergence and spread of ciprofloxacin-resistant Staphylococcus aureus at the Atlanta VA Medical Center because many isolates of interest were nontypeable by phages and harbored few plasmids useful as strain markers. Chromosomal DNAs of selected S. aureus isolates were digested initially with 20 different restriction enzymes. EcoRI appeared to give the best discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 51 publications
0
38
0
2
Order By: Relevance
“…In the present study, 4 of the 59 S. aureus isolates were nonreactive by phage typing, and 3 produced results during the study that differed from the original typing results. Approximately 20% of isolates submitted to CDC for typing are nonreactive by using the international phage typing set (16a); other studies suggest much higher percentages (5,17,20,30,37,42). Given our results and the time and labor required to maintain phage stocks and propagating strains, we concluded that bacteriophage typing is not a cost-effective method of typing S. aureus for most clinical laboratories, particularly since other available methods can be used to type a broader range of other microorganisms.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In the present study, 4 of the 59 S. aureus isolates were nonreactive by phage typing, and 3 produced results during the study that differed from the original typing results. Approximately 20% of isolates submitted to CDC for typing are nonreactive by using the international phage typing set (16a); other studies suggest much higher percentages (5,17,20,30,37,42). Given our results and the time and labor required to maintain phage stocks and propagating strains, we concluded that bacteriophage typing is not a cost-effective method of typing S. aureus for most clinical laboratories, particularly since other available methods can be used to type a broader range of other microorganisms.…”
Section: Discussionmentioning
confidence: 69%
“…Bacteriophage typing has been used for typing S. aureus for many years, but its limitations are clearly recognized (5,20,30,37,42,45). In the present study, 4 of the 59 S. aureus isolates were nonreactive by phage typing, and 3 produced results during the study that differed from the original typing results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one drawback of the method is that markers of antibiotic resistance are often carried by labile or movable genetic elements (e.g., plasmids or transposons) whose selection of expression may depend on environmental conditions. Moreover, since the advance of DNA-based typing methods, it has been repeatedly shown that MRSA isolates which were indistinguishable by antibiotic susceptibility tests could be discriminated on the basis of their genotypes (3,5,12,13,15,16). Thus, antibiogram typing is considered to have poor discriminatory power and is used by microbiologists only in the first instance for rapid screening of the similarities between different clinical isolates.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Outbreaks of infection caused by MRSA have timeconsuming and expensive consequences, and genetic analysis is useful, since it can be used to determine the route and origin of MRSA infection [3]. Currently available laboratory methods for determining DNA fragment sizes or sequences in MRSA isolates include Southern blotting [4], ribotyping [5], polymerase chain reaction (PCR) [6], and pulsed-field gel electrophoresis (PFGE) [4,7]. PFGE has become the most common tool for the rapid discrimination of MRSA strains due to its convenience, reliability, and cost-effectiveness [8,9].…”
Section: Introductionmentioning
confidence: 99%